The Copenhagen Hip and Groin Outcome Score (HAGOS): development and validation according to the COSMIN checklist. Issue 6 (10th April 2011) - Thorborg, K; Hölmich, P; Christensen, R; Petersen, J; Roos, E M
Abstract : Background: Valid, reliable and responsive Patient-Reported Outcome (PRO) questionnaires for young to middle-aged, physically active individuals with hip and groin pain are lacking. Objective: To develop and validate a new PRO in accordance with the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) recommendations for use in young to middle-aged, physically active patients with long-standing hip and/or groin pain. Methods: Preliminary patient interviews (content validity) included 25 patients. Validity, reliability and responsiveness were evaluated in a clinical study including 101 physically active patients (50 women); mean age 36 years, range 18–63 years. Results: The Copenhagen Hip and Groin Outcome Score (HAGOS) consists of six separate subscales assessing Pain, Symptoms, Physical function in daily living, Physical function in Sport and Recreation, Participation in Physical Activities and hip and/or groin-related Quality of Life (QOL). Test–retest reliability was substantial, with intraclass correlation coefficients ranging from 0.82 to 0.91 for the six subscales. The smallest detectable change ranged from 17.7 to 33.8 points at the individual level and from 2.7 to 5.2 points at the group level for the different subscales. Construct validity and responsiveness were confirmed with statistically significant correlation coefficients (0.37–0.73, p < 0.01) for convergent construct validity and for responsiveness from 0.56 to 0.69, p < 0.01. Conclusion: HAGOS has adequate measurement qualities for the assessment of symptoms, activity limitations, participation restrictions and QOL in physically active, young to middle-aged patients with long-standing hip and/or groin pain and is recommended for use in interventions where the patient's perspective and health-related QOL are of primary interest. Trial registration: ClinicalTrials.gov NCT00716729